ANALISIS MODAL SUMBER DAYA MANUSIA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN KARANGASEM - I Gusti Ayu Wahyu Sugandi; Ni Made Tisnawati (E-Jurnal Ekonomi Pembangunan, 2023)
Development regulations are tried to gain considerable financial boom through utilising the ability inside a selected region. The goal of this studies is to investigate the outcomes of the extent of participation of the productive-age populace, instructional attainment, open unemployment charge, and poverty degree at the financial boom in Karangasem Regency. This studies specializes in the location of Karangasem Regency. The sort of facts applied on this studies is secondary facts, received from the Central Bureau of Statistics (BPS) of Bali Province, BPS Karangasem Regency, in addition to different reassets together with financial books and journals. Panel statistics regression evaluation is hired on this study, which makes use of panel statistics in its evaluation. The effects of the evaluation exhibit that the extent of participation of the productive-age populace has a fantastic and considerable partial impact on financial boom in Karangasem Regency. However, instructional attainment does now no longer have a fantastic and considerable impact. The open unemployment charge has a terrible and considerable partial impact, even as the poverty degree has a terrible and considerable partial impact on financial boom in Karangasem Regency.